Size of the intracellular circular Epstein-Barr virus DNA molecules in infectious mononucleosis-derived human lymphoid cell lines. - Adams, A (1979)
The size of non-integrated circular Epstein-Barr virus (EBV) DNA molecules isolated from seven different human lymphoblastoid cell lines of infectious mononucleosis origin has been determined by sedimentation analysis and by direct contour length measurements on electron micrographs. Six lines had intracellular circular EBV genomes of the same size as linear virion DNA molecules. The seventh line, established with the B95-8 strain of EBV, was the only one found to have circular EBV DNA molecules significantly smaller than virion DNA. The data show that intracellular EBV DNA circles of reduced size do not generally occur in infectious mononucleosis-derived cell lines.